Inteligencia emocional: el reto de la educación actual - La Puente Tapia, Lía Marilú (2014)
Emotional education is a tendencythat searches to answer unmet socialneeds in school subjects. Theoreticalfoundation is based on emotion concept,emotion theories, neurosciences,multiple intelligences theory, emotionalintelligence, among others. This articleshows the need of considering such ideasin educational performance.